PENGARUH PROMOSI, KUALITAS PRODUK DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN MAHASISWA MEMILIH IPHONE111 - Rejifzi Difigradez; Andreas Ari Sukoco (Department of Management - Institut Shanti Bhuana, 2024)
This research aims to find out whether promotion, product quality, brand image influence students' decisions in choosing iPhone 11. This research uses a quantitative approach using primary data and secondary data. The sampling technique used was purposive sampling by looking at the criteria for student respondents who had ever purchased or used an Apple iPhone 11 brand cellphone product. To test the questionnaire, validity and reliability tests were used. The research results show that iPhone 11 enthusiasts are not only women. There are also many men who use this product, but the majority of those who use the iPhone 11 are mostly women with an average monthly expenditure of IDR 1,000,000 – IDR 2,000,000. The validity test results were also declared good and met the standards because the results obtained were greater than the predetermined value, namely 0.50, so they were declared valid for research. Hypothesis testing shows that promotion, product quality and brand image influence purchasing decisions